From engagement to competency: The pathway to making disability naïve frontline workers competent in the delivery of an evidence-based autism intervention in New Delhi, India - Naithani, Lavangi; Sangwan, Priya; Roy, Sanjana Guha; Menon, Sreepriya; Azar, Zakiya; Lakhera, Shweta; Kumar, Divya; Abhilashi, Minal Kakra; Roy, Reetabrata; Vajaratkar, Vivek; Taylor, Carol; Patel, Vikram; et al. (Frontiers in Psychiatry, 2022)
BACKGROUND: As countries like India experience improved access to maternal and infant care, an epidemiological transition, the health systems needs to refocus on develop services that enable all children to thrive. A key demographic which needs to be supported are children with disabilities, such as autism. With an estimated prevalence of one percent, there are over five million young children who need services to support their needs. However, the paucity of specialist care makes access to interventions difficult. In this context a public health research not-for-profit is evaluating the effectiveness of the task-sharing approach to support the delivery of an evidenced social communication intervention for young children with autism. This paper describes the process of engaging and training the non-specialist frontline Accredited Social Health Activists (ASHAs), who are embedded within the Ministry of Health and Family Welfare under the Delhi State Health Mission, to deliver a complex intervention for autism to inform the future scalability of services for neurodevelopmental disorders. METHODS: The present study describes the process which included i) engagement meetings, ii) recruitment, iii) training, iv) internship and v) competency evaluation. The shortlisted ASHAs received a seven-day classroom training followed by an internship period with practice cases. Finally, competency assessments, comprising of a test of knowledge and skills through role-plays, was administered. RESULTS: 23 Primary Urban Health Centres across seven districts of Delhi were approached and 408 ASHAs were engaged in initial meetings. Telephonic screening with 127 ASHAs resulted in 72 ASHAs being selected for in-person interviews. Of the 45 ASHAs who attended, 33 were shortlisted for training and 18 completed it. 15 ASHAs entered the internship of which 7 ASHAs achieved competency. CONCLUSION: There was significant attrition along the pathway to having a competent non-specialist worker deliver a complex autism intervention. The lessons learnt from this process can inform the possibility of developing a cadre of disability specific frontline health workers who can deliver evidence based interventions for neurodevelopmental disorders under supervision.